Predictors of quality of life and depression in older people living in temporary houses 13 months after the Wenchuan earthquake in western China: A cross‐sectional study. (15th March 2017) - Xie, Xia; Chen, Yanling; Chen, Hong; Au, Alma; Guo, Hongxia
Abstract: In this study, we explored the predictors of quality of life and depressive features in older people living in temporary housing 13 months after the Wenchuan earthquake in western China. Anonymous data were collected via questionnaires in a cross‐sectional survey of 189 older people living in temporary housing 13 months after the earthquake. To explore the predictors of the outcomes of interest, Pearson correlation and multiple linear regression analysis were used. The results indicated that interests/hobbies, subjective support, and family function were positive predictors of quality of life, whereas instrumental activities of daily living and depressive symptoms were its negative predictors. In addition, we found that a higher level of instrumental activities of daily living predicted a greater likelihood of depression. These results suggested that developing strategies to decrease the instrumental activities of daily living score of these people helps improve their quality of life and depression. To enhance the quality of life of these individuals, healthcare providers should also focus on developing their interests/hobbies and provide them with adequate social support, especially subjective support.